Isolation and well-being in the time of lockdown - Lise Bourdeau-Lepage; Balázs Kotosz (REGION, 2021)
In response to the Covid 19 health crisis, the French government has imposed various measures, referred to as social-distancing measures, including a lockdown with the primary objective of reducing face-to-face interactions between people in order to limit the spread of the virus. This paper seeks to determine whether social-distancing measures and lockdown lead to social isolation for certain groups of people and if they have an impact on French people's well-being. First, it reveals that feelings of social isolation have substantially increased in France during the lockdown and regional differences have occurred. Second, it shows a change in the geography of well-being in France induced by lockdown - with Southerners, originally the happiest, exhibited a strong decline in well-being. Third, estimations show that acclimation to social isolation slows the decline in well-being during lockdown; and that the increase in people's feelings of social isolation during lockdown is a factor which negatively impacts their level of well-being. Fourth, it reveals certain positive influences of residence geographic location on changes in well- being levels.
Keywords: I31; I30; I14; 330; health; France; French regions; social isolation; well-being; Covid-19